1420. A One Health Approach Examining the Potential Linkage between Agricultural Livestock and Human Antibiotic Resistance at the Watershed Level. (31st December 2020) - Donner, Linsey M; Li, Xu; Snow, Daniel D; Sangster, Jodi L; Staley, Zachery R; Amandus, Loralee J; Mathews, Wayne A; Bartelt-Hunt, Shannon
Abstract: Background: Antibiotic resistance is a significant public health threat and widespread use of antibiotics in agriculture is increasing the concern about agricultural contributions to the dissemination of antibiotic resistant bacteria. Of concern is the level of exposure to antibiotics and antibiotic-resistant bacteria in the watershed. Consequently, adopting a One Health approach to measure antibiotic levels and identify antibiotic resistance gene (ARG) transfer at the human, animal and environmental interfaces is essential to better understand how antibiotic resistance is spread. Methods: In this project, antibiotic levels were measured using passive organic chemical integrative samplers (POCIS) for 30-day periods from August – November 2018 from Elkhorn River and Shell Creek watersheds in Nebraska (Figure 1). In addition, whole genome sequences of bacterial isolates cultured from the watersheds were assessed to identify ARGs present on mobile genetic elements (MGE) that had >95% similarity to mobile ARG present in isolates recorded in the NCBI GenBank database was identified using ResFinder. Figure 1. Sampling locations within the two watersheds. Results: The study demonstrated significant antibiotic levels present throughout the watershed, with five of them associated with human usage (Table 1). In addition, seasonally based drug-resistant bacterial species was associated with specific antibiotic levels in the watershed (Figure 2). Mobile ARGs were detected in 87.5% of isolates collected from the Elkhorn River and 80.0% within Shell Creek (Figure 3). Table 1. Pharmaceutical levels in the watershed Figure 2. Antibiotic levels and drug-resistant bacteria in the watershed Figure 3. Antibiotic resistance observed from each isolate at every sampling date and site. A colored bar denotes that resistance to that antibiotic was observed. Conclusion: These results present evidence of transfer of highly mobile ARGs between environment, clinical, and animal-associated bacteria and highlight the need for a One Health perspective in assessing the spread of antibiotic resistance. The presence of significant levels of antibiotics persisting in this agricultural watershed points out the need for ongoing monitoring of compliance with the Food and Drug Administration (FDA) recommendation of veterinarian oversight of the use of antibiotics in the use of veterinary feed directive applications. Disclosures: All Authors : No reported disclosures